Faktor penentu yang mempengaruhi penggunaan layanan internet banking - Ellen Theresia Sihotang (Faculty of Economics and Business Mulawarman University, 2016)
This study aims to analysis the important factor that influence the use of internet banking according to Booklet Perbankan Indonesia 2016 and the implication for the marketing of internet banking services. Security has become a determining factor which affecting the use of internet banking services. It is important for the bank to find out how to maintain the customers who have used the internet banking services in order to encounter competition with a variety of banking services distribution channels innovation. This research used purposive and snow ball sampling. Data collection is done by distributing questionnaires to individual users of internet banking in Indonesia. The results showed that security as the important determining factors that influence to use internet banking, while auxiliary features do not. Keywords: Internet banking, Consumer behavior, Security, Auxiliary features.